(untitled) (Journal of Surgical Sciences, 2019)
Chronic anal fissure is a non healing ulcer in the anoderm appearing as a painful tear below the dentate line. There are debates about the efficacy of different treatment options for chronic anal fissure. This review aims to evaluate existing and newer treatment modalities. Aspects of chronic anal fissure aetiology and pathogenesis are also reviewed. Glyceryl trinitrate (GTN) ointment, Diltiazem ointment can be used as first line and Botulinum toxin (BTX) injection as second line pharmacological treatment. The effects of these chemicals are not permanent with higher fissure recurrence rates. Lateral internal sphincterotomy is the operative treatment of choice for fissures with high anal tone. Flap anoplasty should be done for fissures with normal anal tone especially in female patients. Both surgical procedures can be used as primary treatment option. The newer treatment options like gonyautoxin, controlled balloon anal dilatation, closed anal spand fissurotomy need more research. Perineal support device can be used as an adjunct to other treatment modalities. Journal of Surgical Sciences (2015) Vol. 19 (2) : 67-71